A Comparative Review of Communication Technologies for Asset Tracking in Healthcare Facilities - Al-Maktary, Omar; Susanto, Misfa (MSD Institute, 2025)
Efficient asset tracking in healthcare facilities is essential to reduce delays, prevent equipment loss, and optimize operational workflows. This study systematically reviews four widely used technologies: Radio Frequency Identification (RFID), Near Field Communication (NFC), Global Positioning System (GPS), and Bluetooth Low Energy (BLE), based on six criteria: cost, accuracy, range, energy efficiency, ease of deployment, and scalability. RFID and NFC offer high accuracy in short-range use cases, but RFID requires substantial infrastructure, while NFC is limited by its manual operation. GPS is highly effective for outdoor tracking, though it struggles indoors. BLE provides a strong balance across all criteria and supports long battery life, making it suitable for large-scale indoor tracking. The review incorporates real-world case studies and proposes hybrid IoT-based systems that combine these technologies to achieve comprehensive coverage. Future research should focus on seamless indoor-outdoor handoff, energy-efficient synchronization, and the use of machine learning for signal optimization.